Aplicabilidade e eficácia dos direitos fundamentais sociais trabalhistas: a eficácia horizontal nas relações de trabalho - Daher, Chafic Krauss (2016)
The effectiveness of fundamental rights between the contracting parties of labor relations, while the legal and private, is presented as a relevant issue to be considered in the light of the current dynamics of subordinating relations between employers and employees. Such a scenario seems highly conducive to serious violations of fundamental rights of the parties involved, especially the workers because they are the most vulnerable part of such relationships. In search of maximum effectiveness they demand, the fundamental rights of employers and workers cause conflicts or collisions, assuming primary function of the review of the effects of fundamental rights in such relationships. The evolution hermeneutics grounded in normative force of the Constitution and the subsequent constitutionalization of private law, including the Labor Law, produced significant effects in the field of social labor. From the analysis of doctrine and jurisprudence, explores issues such as the conceptual delimitation and the fundamental procedural and substantive fundamental rights, adopting a classification for these duties. Study it was also necessary limits to fundamental rights, since no absolute rights and are subject to limitations or restrictions for the benefit of other property or rights equally protected by constitutional norms. Addressing to the system of fundamental rights established by the catalog of the Constitution of 1988, we study the applicability and effectiveness of fundamental rights within the legal and private relations, especially relations of employment. After some brief remarks about the so-called vertical efficiency, understood as the commitment of governments to respect, protect and promote fundamental rights, proceeds to the horizontal analysis of the effectiveness of such duties, a term used to describe the incidence of these rights within the interprivadas relations. As in any relationship interprivadas, the rights and liberties guaranteed to citizens are fully maintained in working relationships perhaps celebrated. Although there are doctrinal trends which deny fundamental rights application in the relationships between private persons, or even admitting that the current, only an indirect way to recognize or mediate in private labor relations only accepting direct or immediate effectiveness as a general rule enable effective protection of fundamental rights of workers. Consequently, these rights may come into conflict or collision with other rights, property values and also constitutionally protected, leaving the Judiciary to fix them. To develop such a function, the more important the use of certain instruments arrangers of the tension points in the existing law, the principle of proportionality or reasonableness and technical or weighing up the balance in the collision of fundamental rights in labor relations.